2021
DOI: 10.1111/bph.15651
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics reveals biomarkers in human urine and plasma to predict cytochrome P450 2D6 (CYP2D6) activity

Abstract: conceived and designed the clinical trial. G.M, J.D. and A.M. performed the clinical trial. G.M. and Y.G. performed CYP2D6 genotyping. G.M., N.B., T.J. and A.T. performed metabolomic analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 61 publications
(99 reference statements)
6
31
0
Order By: Relevance
“…For methods which acquire non-selective full-scan HRMS data, these data can be retrospectively reprocessed for compounds that were not targeted in the initial analysis, without the need of re-extraction and re-analysis of the sample. Solanidine and five solanidine metabolites (M412, M414, M416, M432, and M444), which were recently described by Magliocco et al [ 11 ], were identified in the HRMS data files by accurate mass (the protonated molecular ion was present within a mass tolerance of 5 ppm) and isotope ratio. The MS/MS spectrums of the identified peaks, acquired using the full-scan ddMS2 mode, all showed a major fragment at m/z 98.0967, which further confirmed detection of the same solanidine metabolites as described previously [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For methods which acquire non-selective full-scan HRMS data, these data can be retrospectively reprocessed for compounds that were not targeted in the initial analysis, without the need of re-extraction and re-analysis of the sample. Solanidine and five solanidine metabolites (M412, M414, M416, M432, and M444), which were recently described by Magliocco et al [ 11 ], were identified in the HRMS data files by accurate mass (the protonated molecular ion was present within a mass tolerance of 5 ppm) and isotope ratio. The MS/MS spectrums of the identified peaks, acquired using the full-scan ddMS2 mode, all showed a major fragment at m/z 98.0967, which further confirmed detection of the same solanidine metabolites as described previously [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Solanidine and five solanidine metabolites (M412, M414, M416, M432, and M444), which were recently described by Magliocco et al [ 11 ], were identified in the HRMS data files by accurate mass (the protonated molecular ion was present within a mass tolerance of 5 ppm) and isotope ratio. The MS/MS spectrums of the identified peaks, acquired using the full-scan ddMS2 mode, all showed a major fragment at m/z 98.0967, which further confirmed detection of the same solanidine metabolites as described previously [ 11 ]. The same MS/MS fragmentation pattern was also evident for two additional peaks, M402 and M440, which were discovered by use of the metabolomics software Compound Discoverer 3.2 (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous drugs are metabolized by an isoenzyme family called cytochrome P450 (CYP), which is mostly found in the endoplasmic reticulum of liver cells [ 84 ]. About 25% of all medications used in clinical practice are metabolized by the cytochrome P450 2D6 (CYP2D6) enzyme [ 119 ]. The drug-metabolizing enzyme Cytochrome P450 2D6 (CYP2D6) is produced by the CYP2D6 gene [ 152 ].…”
Section: Control Challengesmentioning
confidence: 99%
“…7 In the field of personalized medicine, there is considerable interest in endogenous compounds metabolized through drug-metabolizing enzymes. 8,9 Indeed, CYP450 enzymes are subject to high intra-and interindividual variability, requiring effective and nonburdensome tools to characterize their activity in a given subject at a specific time. 10 The use of endogenous markers offers numerous advantages over exogenous probes to phenotype CYP450 activity.…”
Section: Introductionmentioning
confidence: 99%